Rehabilitation using immediate dentures on teeth with periodontal abnormalities: Rehabilitation using immediate dentures on teeth with periodontal abnormalities - Hidayat, Muh. Ichram Arief; Ikbal, Muhammad; Jubhari, Eri Hendra (Makassar Dental Journal, 2025)
Tooth loss can affect the aesthetics, function, psychology and social condition ofpatients, especially in the front teeth. This can be prevented with immediate denture prosthetic rehabilitation to avoid the tooth loss phase. This article reports the success of lo-wer jaw immediate denture treatment incases of tooth extraction caused by periodontal abnormalities in order tomaintain function and aesthetics in patients. Clinical examination showed tooth loss in 31, 34, 35, 36, 37, 38, 43, 44, 45, 46, and 48, accompanied by severe resorption of the alveolar ridge. Extraction of teeth 33, 32, 41, and 42 was performed after the denturewas fabricated. It was concluded that immediate denture treatment of the lower jaw can maintain the function and aesthetics of patients with tooth extraction caused by periodontal disorders.